Acinetobacter spp. in food and drinking water – A review. (May 2021) - Carvalheira, Ana; Silva, Joana; Teixeira, Paula
Abstract: Acinetobacter spp. has emerged as a pathogen of major public health concern due to their increased resistance to antibiotics and their association with a wide range of nosocomial infections, community-acquired infections and war and natural disaster-related infections. It is recognized as a ubiquitous organism however, information about the prevalence of different pathogenic species of this genus in food sources and drinking water is scarce. Since the implementation of molecular techniques, the role of foods as a source of several species, including the A cinetobacter baumannii group, has been elucidated. Multidrug resistance was also detected among Acinetobacter spp. isolated from food products. This highlights the importance of foods as potential sources of dissemination of Acinetobacter spp. between the community and clinical environments and reinforces the need for further investigations on the potential health risks of Acinetobacter spp. as foodborne pathogens. The aim of this review was to summarize the published data on the occurrence of Acinetobacter spp. in different food sources and drinking water. This information should be taken into consideration by those responsible for infection control in hospitals and other healthcare facilities. Highlights: Foods are potential sources of dissemination multidrug resistant Acinetobacter . Acinetobacter may colonize the digestive tracts through the consumption of food. Limited information on association of Acinetobacter with foodborne illnesses.